Artificial Photosynthesis at Dynamic Self‐Assembled Interfaces in Water. Issue 1 (10th November 2015) - Hansen, Malte; Troppmann, Stefan; König, Burkhard
Abstract: Artificial photosynthesis is one of the big scientific challenges of today. Self‐assembled dynamic interfaces, such as vesicles or micelles, have been used as microreactors to mimic biological photosynthesis. These aggregates can help to overcome typical problems of homogeneous photocatalytic water splitting. Microheterogeneous environments organize catalyst–photosensitizer assemblies at the interface in close proximity and thus enhance intermolecular interactions. Thereby vesicles and micelles may promote photoinitiated charge separation and suppress back electron transfer. The dynamic self‐assembled interfaces solubilize non‐polar compounds and protect sensitive catalytic units and intermediates against degradation. In addition, vesicles provide compartmentation that was used to separate different redox environments needed for an overall water splitting system. This Minireview provides an overview of the applications of micellar and vesicular microheterogeneous systems for solar energy conversion by photosensitized water oxidation and hydrogen generation. Abstract : The interface makes the difference : Self‐assembled dynamic interfaces like micelles and vesicles help solving challenges of homogeneous solar energy conversion systems by self‐organization, compartmentation and protection of catalytic units. This Minireview highlights the progress in the utilization and functionalization of micellar and vesicular systems for light‐driven oxygen or hydrogen evolution.